Departmental action teams: Empowering students as change agents in academic departments - Reinholz, Daniel Lee; Pawlak, Alanna; Ngai, Courtney; Pilgrim, Mary (International Journal for Students as Partners, 2020)
Supporting and sustaining positive educational change is an area of increasing focus in higher education and remains a persistent challenge. Using student partnerships is one promising way to help promote these much-needed changes. This case study focuses on Departmental Action Teams (DATs), which are groups of faculty, students, and staff working together in the same department to make sustainable improvements to undergraduate education. Here we focus on DATs from four different departments, across two research-intensive universities in the USA, to draw attention to the important roles that students play as change agents in these groups. We also reflect upon the inherent challenges in building partnerships that incorporate meaningful power sharing to effect educational change